The Impact of Pre and Post-Mergers and Acquisitions on the Financial Performance of Selected Banks in Pakistan - Fahad, Muhammad; Hamid, Kashif; Aslam, Maryam; Saeed, Muhammad Yasir; Abbas, Yawar (iRASD Journal of Economics, 2025)
The purpose of this study is to investigate the financial performance of merging banks in Pakistan in a pre and post-scenario to identify the impact of key indicators on the performance of acquirer company. For this purpose, data for 4 banking companies have been taken from financial year 2005 to 2022. Banking companies include Meezan Bank Limited (MBL) Muslim Commercial Bank Limited (MCB) Al Baraka Bank (Pakistan) Limited (ABPL) and Bank Islami Pakistan Limited (BIPL). Paired sample t-tests and regression analysis was used to identify significant differences and impact on pre and post-merger. Results revealed that there were significant positive differences in specific financial indicators as Return on Assets on MCB only. However, results indicated in pair sample t-test that Net Interest Margin was significant for MCB and ABPL, whereas Debt to Equity was significant for all banks. Further Capital Adequacy Ratio revealed significant results for MBL and ABPL but Total Loan to Total Deposit has significant outcome for BIPL only. It is important that results for Non-Performing Loans to Total Loans were significant for MBL, MCB and BIPL but Earning per Share has been found significant for MBL. The key important indicators of Market Price per Share is found significant for all banks. Dividend per share has significant outcome for ABPL only. Regression results revealed that in post-merger capital adequacy ratio, earning per share has positive but dividend per share and market price per share has significance negative impact on return on assets at (p<0.05) but no significant impact was found pre-merger context. The findings provide valuable insights for policymakers to strategically focus on future corporate restructuring and to ensure financial stability.